Social and Geographical research in the republic of Kazakhstan with the use of GIS technologies - Gulnara Nyussupova; Aisulu Kalimurzina; Roza Kelinbayeva (European Journal of Geography)
The article deals with the dynamics of the main indicators of socio-geographical processes of the Republic of Kazakhstan from 1999 to 2014. The article is based on statistical data from 1999 to 2014 with an emphasis on 1999, 2009 (the first and second censuses of independent Kazakhstan) and 2004, 2014. The territorial analysis of the socio-geographical processes includes such indicators as population size, infant mortality, and life expectancy, the level of health care, education level, and provision of the housing of the population. The main conclusions are: 1. Kazakhstan is characterized by the increase in population due to natural growth and a positive balance of migration; 2. The aging of the population, which led to the increase in the unfavorable side of the indicator of the demographic load and the balance of labor resources; 3. Low life expectancy in comparison with the developed countries; high infant mortality rate. At the same time, Kazakhstan has almost 100% literacy rate of the population and high coverage of the population by education